OUTCOME OF CANALICULAR REPAIR: OUR EXPERIENCE AT HAYATABAD MEDICAL COMPLEX (The Research of Medical Science Review, 2025)
Background: Canalicular injuries, which may occur due to facial trauma, surgical procedures, remain a considerable source of difficulty in ophthalmic practice, as they play an integral role in tear drainage. Failure to repair these injuries in a time-efficient and effective manner can result in chronic epiphora, infections, and ocular surface complications, negatively affecting a patient’s quality of life. Surgical technique has evolved, with improved outcomes reflecting the usability of monocanalicular & bicnalicular stenting; however, variability in success rates and complications remain evident throughout the literature. Objective: To evaluate the outcomes of canalicular repair in a tertiary care setting, focusing on success rates, complications, and factors influencing prognosis. Material & Methods: This prospective observational study was carried out in the Ophthalmology Unit of Hayatabad Medical Complex, Peshawar, from January 1st 2021 to November 30th 2024. Study objective: To assess outcomes of canalicular repair in patients with canalicular injuries. The cohort comprised 34 patients aged between 05–60 years with canalicular injuries who underwent surgical repair during the study period. Results: Primary anastomosis with canalicular stenting (using common silicon DCR tubes, “Bodkin tube”) was the technique of choice for all the cases. Majority of the patients were male (73.5%, n=25), and the remaining were female (26.5%, n=9). The most common cause of canalicular injury was facial trauma (88.2%, n=30), followed by animal bites (5.9%, n=2). The remaining 02 cases was due to other injuries. Most injuries involved the lower canaliculus (76.5%, n=26), upper canaliculus was involved in (17.6%, n=6), while both the canaliculi were involved in the remaining 2 (5.9%) cases. Conclusion: Early surgical intervention of canalicular injuries yields a 97% success rate with canalicular stenting. Timely intervention is essential; repairs completed within 48 hours significantly improves the outcome. The low rate of complications speaks to the safety of these techniques.